Chinese-Bumiputera Partnership In Technology-Based Industries In Post NEP And Post NDP Malaysia. - Chin, Yee Wah (2005)
This paper discusses ChineseBumiputera partnership in technology based industries in post National Economic Policy (NEP) and post National Development Policy (NDP) Malaysia.